Structured deposition of animal remains in the fertile crescent during the Bronze Age - Ramos Soldado, José Luis, (Access archaeology., 2016)
The aim of this research is to draw up a literature review of the structured deposits of animal remains during the third and second millennia BC in the Ancient Near East for its subsequent classification and detailed interpretation.